HASIL AKUAKULTUR MANDIRI (HAM), INOVASI PENCEGAHAN STUNTING BAGI MASYARAKAT MISKIN LOKAL ACEH BARAT - Rinawati, Rinawati; Zulfadhli, Zulfadhli; Hayuningtyas, Afwa; Muhsin, Sri Wahyuni; Fadhillah, Radhi (Jurnal Abdi Insani, 2024)
Stunting is a condition of growth failure in children under five due to inadequate nutritional intake. The main characteristic of stunting is that the child's height is not age-appropriate, which is shorter than children of the same age. Steps to prevent stunting can be taken in various ways, including educational activities, nutrition fulfillment, and anthropometric training. Training on using anthropometry during measurement is expected to make the data collection of children's nutritional status more accurate, and the fulfillment of nutritional sources through local innovations such as independent aquaculture can contribute to providing protein sources. This community service activity aims to increase the understanding of cadres and mothers of toddlers in Gampong Pasi Jeumpa about stunting prevention. Budikdamber training aims to enable the community to fulfill protein as a source of nutrition independently. Implementing this program is through education, counseling, and training. The activity stages include several vital steps, including program preparation, program socialization with partners, and implementation of education and training. Assistance was provided to understand the training and education activities better. The evaluation was conducted to assess the overall success of the program. The activity results showed increased participants' understanding, with the percentage of understanding increasing from 55% (pre-test) to 91% (post-test). Participants better understood the factors that cause stunting and the steps to prevent stunting. Participants became more aware of how to measure using anthropometric tools. Participants also became more aware of how to cultivate fish on a small scale to fulfill the protein and vitamin needs needed for stunting prevention. [This service activity increased participants knowledge of stunting problems and improved measurement skills using anthropometric tools. Participants understand the proper cultivation steps so that the fish produced can be a source of nutrients needed.